RELEVANSI DOKUMEN ABU DHABI BAGI KEHIDUPAN BERAGAMA DI INDONESIA - Situmorang, Agnes Regina; Dewantara, Agustinus Wisnu (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
Religious diversity is an undeniable reality in Indonesia, a country with a multi-religious and multicultural society. This diversity is a strength, but also poses challenges, especially in the form of religious intolerance and conflict. The Catholic Church, under the leadership of Pope Francis, has been actively promoting interfaith dialogue, culminating in the Abu Dhabi Document on Human Fraternity, co-signed with Grand Imam Al-Tayyeb. This study aims to examine the relevance and application of the Abu Dhabi Document in promoting religious tolerance and dialogue in Indonesia. This study uses a qualitative approach with document analysis. Research findings show that the principles outlined in the Abu Dhabi Document provide valuable insights for strengthening peaceful religious coexistence in Indonesia. If implemented effectively, the document can serve as an educational tool for interfaith dialogue and a means to strengthen harmonious religious life.